The more the merrier? Macroprudential instrument interactions and effective policy implementation - Marco Lo Duca; Mehdi Bartal; Edita Giedraitçe; Peik Granlund; Niamh Hallissey; Pavol Juréca; Charalampos Kouratzoglou; Petra Lennartsdotter; Diana Lima; Mara Pirovano; Algirdas Prapiestis; Martin Saldias; et al. (European Central Bank (ECB), 2023)
Macroprudential policies since the global financial crisis have been central to safeguarding financial stability. Despite the increasing use of multiple policy instruments, a detailed understanding of interactions among them is still needed to assess how instrument combinations can enhance the effectiveness of macroprudential action. This paper proposes a conceptual framework for informing the choice of combinations of macroprudential instruments, looking at the role of micro and macroeconomic transmission channels, interactions across policy objectives, the importance of country specificities and linkages with other macroeconomic or supervisory policies. It also reviews considerations related to circumvention, leakages, time of activation and communication of policies, all of which may affect the desirability of different combinations of macroprudential instruments. The paper also discusses a possible operational use of combinations of macroprudential instruments to address selected risks and provides a rich analysis of instrument interactions within the categories of borrower-based and, respectively, capital-based measures. The paper concludes that the combinations of capital and borrower-based instruments ensures a comprehensive coverage of different systemic risks and entail important synergies.
Keywords: G21; G28; 330; financial stability; macroprudential policy; banks